Vloga kronične in akutne moči pri javnem sramotenju na spletnih socialnih omrežjih - Svetek, Mojca (Psihološka obzorja (Ljubljana), 2025)
Public shaming on social networking sites has become an increasingly widespread form of cyberbullying, with profound and far-reaching consequences for those affected. A key characteristic of online public shaming is the power imbalance between the target of shaming and the mob. The individuals who are part of the mob may be individually powerless compared to the target, but as a mob they exert enormous pressure on the target. Thus, participation in public shaming is an opportunity to experience power, regardless of one’s actual level of power (chronic power). In this study, we examined the interaction effect between chronic and acute power on hostility, support for public shaming, and actual public shaming behaviour. Participants (N = 192, UK social media users) were randomly assigned to conditions of high or low acute power and shown a controversial online post by a stranger to which they could respond. Results showed that chronic power alone was not associated with hostility, support for public shaming and ostracism, or with shaming behaviour; however, the effects emerged in interaction with acute power, which we manipulated experimentally. Participants reported higher levels of hostility when chronic and acute power conditions were not aligned, and this hostility predicted greater support for shaming and ostracising the target. This effect was more pronounced in chronically powerless individuals. The study underscores the importance of distinguishing between different forms of social power and contributes to a better understanding of the empirically underexplored role of social power in public shaming.
Keywords: cyberbullying; družbena omrežja; ethics; etika; influencers; internet; social networks; spletno nasilje; vplivneži